ANALISIS PERAN MEDIATOR DALAM MENANGANI KASUS PERCERAIAN ( Studi Kasus Di Pengadilan Agama Jombang Tahun 2023) - Ulan Agung; Abdullah Afif (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Mediation is a kind of alternative conflict resolution in which a neutral third party (the mediator) helps the disputing parties to an agreement without having final say over the matter. In order to find out how effective mediation is, particularly in divorce cases heard at the Jombang religious Court, and to lower the divorce rate, the mediator acts as the central figure in resolving cases. As shown by the low success rate of mediation in 2,938 divorce cases, mediation is actually less successful when dealing with these types of instances. Using a case study methodology, this research employs empirical juridical research. Direct interviews with judges and mediators who were not judges, as well as observation, were used to gather data. Researchers in this work use a descriptive qualitative analysis strategy for their data. The study findings revealed that the involvement of mediators in the implementation of mediation in divorce cases was subpar and ineffective; just 16 out of 2,938 cases, or 0.5%, were effectively mediated. Because of factors such as a lack of self-awareness, egotism, and a lack of desire to be peaceful, the fact that mediation is unpleasant, and the misconception that it is only a procedure, a unique category of impartial mediators is required to improve mediation outcomes. Explain to each party involved in a dispute why mediation is important.